Regional stratigraphy, facies distribution, and hydrocarbons potential of the Oligocene strata across the Arabian Plate and Western Iran - Fadhil N. Sadooni (13790378) (2019)
Major global events during the Oligocene epoch included a climatic change from warm “greenhouse” to a cooler “icehouse” that was accompanied by the onset of Antarctic glaciation. These events led to decline in water temperature, salinity, nutrient supply and oxygen levels, and the extinction of some major fauna and flora. Within the study area, during this epoch, the shrinkage of the Neotethys and the development of the Paratethys, the collision of Arabia with Eurasia and the development of the Zagros mountains and opening of the Red Sea which led eventually to the separation of Arabia from Africa were witnessed. Oligocene sediments are absent from most parts of the Arabian Plate but are well-preserved in western and southwestern Iran. The most well-developed strata are the coral reefs of the Kirkuk Group in northern Iraq and the shallow water carbonates of the Asmari Formation in southwestern Iran. The study area also represents the birthplace of commercial hydrocarbons production in the Middle East from these sediments in Masjid-i-Sulaiman Field in Iran and Kirkuk Field in Iraq at the first decade of the last century. Future exploration for hydrocarbons potential should focus on identifying subsurface coral buildups or clastic strata that are equivalent to the Asmari Formation in Iran. Other Information Published in: Carbonates and Evaporites License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s13146-019-00521-3